Unexpected foreign body in the bladder of a spinal cord injured patient: A case report. (2nd November 2019) - Mengi, Alper; Erhan, Belgin; Kara, Belgin; Yalcinkaya, Ebru Yilmaz
Abstract : Context: Bladder dysfunction is common in patients with spinal cord injuries. Clean intermittent catheterization is a preferred method of neurogenic bladder management among spinal cord injured patients. Some complications may occur due to the use of clean intermittent catheterization. Findings: In this report, we presented a case with an unexpected foreign body detected in the bladder of a patient who used to perform clean intermittent catheterization for her neurogenic bladder management, to our knowledge, which has not been reported in the literature so far. Conclusion/Clinical Relevance: In this case report, we want to emphasis the importance of different kind of foreign bodies remaining in the bladder during clean intermittent catheterization.